Garbage Segregation and Monitoring Using Low-Cost IoT System for Smart Waste Management (Open International Journal of Informatics, 2023)
Waste management is one of the serious issues in maintaining the longevity of life. Managing waste in garbage bins not only requires a systematic garbage segregation policy but also a prevention and control mechanism for human behaviour. With the aid of the low-cost-budget Internet of Things (IoT) approach, managing garbage bins for municipal and town councils become practical, effective, and easy to be enforced. This study proposed a proof-of-concept prototype of a low-cost IoT approach using Raspberry Pi and cheap sensor modules to segregate waste into garbage bins with local alarming and remote notification systems. The systems are capable of detecting metal and non-metal waste so that segregation can be applied, and measuring waste levels in the garbage bin to prevent waste overflow. On top of that, the systems are also able to warn with loudness sound of a mistype waste scanned at the bin lid and send prompt notifications to the remote observer for further actions. The study results from a number of performance testing demonstrated the developed systems can accurately measure waste levels either to be empty, half-filled, or 80% filled when the ultrasonic ranging module sensor is placed 105° inside the bin. This is the best positioning we recommended when working with a bin of size 15 cm in height and 10 cm in width. Finally, we observed that the finest detection results were achieved when the movement of objects are scanned less than 2 cm, but not more than 4 cm away.
Keywords: Smart Garbage; Internet of Things; Smart waste Management; Garbage Segregation